ELIMINATING MASS-FRACTIONATION EFFECTS ON U-PB ISOCHRON AGES WITHOUT DOUBLE SPIKING - Ludwig K.R. (My University, 2001)
The utility of uranium-lead isochrons for dating rocks with a restricted range in U/Pb is limited by any uncertainty in the mass fractionation of the analysis. Double spiking (TIMS) or thallium normalization (ICP-MS) remove much of this limitation, as does the method of Getty and DePaolo (1995) for very young rocks. Optimal use of the 3-D ''Total Pb/U isochron,'' however, is extremely simple to apply, requires only single-spiked TIMS analyses, and essentially eliminates fractionation-related age imprecision for rocks of any age.